Magneto-Rheological Variable Stiffness and Damping Torsional Vibration Control of Powertrain System - Dong, Xiaomin; Li, Wenfeng; Yu, Jianqiang; Pan, Chengwang; Xi, Jun; Zhou, Yaqin; Wang, Xuhong (Frontiers in Materials, 2020)
A novel magneto-rheological variable stiffness and damping torsional vibration absorber (MR-VSDTVB) is proposed, fabricated and tested. According to the test data, the control model of MR-VSDTVB is established. Meanwhile, the analysis of the multi-degree-of-freedom model of the powertrain system provides the key frequency and the rotation speed of the torsional vibration control of the powertrain system and further determines the installation position and structural parameters of MR-VSDTVB. Besides, a human-simulated intelligent controller (HSIC) is developed and numerical simulation of the powertrain system with MR-VSDTVB is carried out. Ultimately, the result verifies the effectiveness of the powertrain system with MR-VSDTVB and the semi-active HSIC algorithm on the torsional vibration control.